The interpretive approach to religious education: challenging Thompson’s interpretation - Jackson, Robert (Journal of beliefs and values, 2012)
In a recent book chapter, Matthew Thompson makes some criticisms of my work, including the interpretive approach to religious education and the research and activity of Warwick Religions and Education Research Unit. Against the background of a discussion of religious education in the public sphere, my response challenges Thompson’s account, commenting on his own position in relation to dialogical approaches to religious education. The article rehearses my long held view that the ideal form of religious education in fully state funded schools of a liberal democracy should be ‘secular’ but not ‘secularist’; there should be no implication of an axiomatic secular humanist interpretation of religions.